Les Papes et le Maghreb aux XIIIème et XIVème siècles Eìtude des lettres Pontificales 1199 á 1419 - Maillard, Clara (Les Papes et le Maghreb aux XIIIème et XIVème siècles : Eìtude des lettres Pontificales 1199 á 1419, 2014)
For the popes it was inevitable to maintain relations with the Arab-Muslim world, of course eastern - Egypt and the Middle East - but also Western - Spain and the Maghreb. Thus in 1199, Innocent III addressed himself to the "Miramolin, king of Morocco". Some two hundred and one letters, written during the 13th and 14th centuries, mostly recorded in the registers of the Vatican Secret Archives, help to clarify the position of the Holy See vis-a -vis the Maghreb. In order to carry out their policy and to maintain ties with the faithful, the Popes wrote to the Christian or Muslim sovereigns, sent messengers across the Mediterranean Sea, encouraged the works of the brothers in this part of the world, A bishopric in Marrakesh. They regularly supported attempts to expand Christianity in North Africa, but this was not their only concern. They also cared about the Christians who lived in the Maghreb, whether they were merchants, mercenaries or captives. The papacy had to reconcile these two aspects and had to adapt to the reality of the life of these communities in the land of Islam. Clara Maillard at the MSH of Nantes on December 8, 2011, her thesis in medieval history entitled "Popes and Maghreb in the XIIIth and XIVth centuries, study of apostolic letters from 1199 to 1419", under the direction of John Tolan , Professor at the University of Nantes. She worked with the RELMIN project in 2014 as a post-doctoral student on the pontifical letters concerning Christians who lived in the Maghreb.